Дослідження проростання насіння на донних осадах з регулюючих басейнів - Якшин, Т. С.; Пікареня, Д. С.; Yakshin, T. S.; Pikarenia, D. S. (Дніпровський державний технічний університет, 2019)
The following abstracts present the results of experiments on the germination of tester plants on water extracts of sediments of regulatory basins from Tsarychans`yy Irrigation System. Water extracts of sediments were studied as fertilizers for growing edible and technical crops of plants.
The study of seed germination on sediments of regulatory basins
Keywords: germination; germinating power; sediments; water weights and extracts; regulatory basin